Piracetam in postconcussion syndrome: preliminary results of a randomized study using SPECT - Agrawal, Deepak; Gowda, NK (Indian Journal of Neurotrauma, 2007)
Aim of this study was to study the changes in regional cerebral perfusion following administration of the drug piracetam using single photon emission computed tomography (SPECT) in patients with postconcussion syndrome (PCS). Twenty consecutive male patients 18–65 years of age, with mild traumatic brain injury and PCS who had an normal initial CT head but an abnormal SPECT scan (carried out within 72 hours of the injury), were included in the study. Patients were randomized to either receive a daily dose of 2.4g of piracetam for six weeks (n = 10) (piracetam group), or no piracetam (n = 10) (control group). A repeat SPECT scan was performed at six weeks of follow up and any subjective improvement in symptoms (if any) noted. While the pre-treatment mean ratio for the piracetam treated group (0.86) and controls (0.85) did not differ significantly (p = 0.304; 95% CI - 0.041,.0136), there was a significant rise in the post treatment ratio in the piracetam group (mean: 0.959) as compared to the controls (mean: 0.882) (p = <0.001; 95% CI -.0114, -0.038). Nine patients (90%) also had improvement in their symptoms of PCS, compared to only three patients in the test group (Fisher exact test; 2 tailed: p = 0.01). Our study suggests that the cerebral perfusion defects seen on SPECT imaging may per se be responsible for the clinical manifestations of PCS. Low-dose piracetam appears to improve regional cerebral blood flow and reverse perfusion abnormalities in these patients. This study paves the way for further randomized, placebo controlled trials with piracetam for more definitive results.
Keywords: closed head injury; concussion; cerebral perfusion; mild traumatic brain injury; neuroprotective agents; post concussion syndrome; piracetam; SPECT